Odor evaluation scales for odor in neoplastic wounds: an integrative review - Marcos Antonio de Oliveira Souza; Nauã Rodrigues de Souza; Jessica Thamires da Silva Melo; Maria Alessandra Campos Absalão Xavier; Gabriela Lopes de Almeida; Isabel Cristina Ramos Vieira Santos
ABSTRACT Objective: Checking for the existence of assessment instruments for odor in neoplastic wounds. Method: Integrative review performed in the databases Lilacs, SCiELO, Ibecs and MedLine, including national and international publications. Results: 15 articles were analyzed, in its majority performed by nurses and being of the revision type. Nine scales were found, of which the majority assesses only the odor intensity. The scale most used to evaluate products and/or bandage covers for neoplastic injuries was the Odor Evaluation Guideline, of qualitative-quantitative nature, that establishes the symptom within four levels; only one of which being validated (Teler scale). Conclusion: The results of this study showed that, currently, there is only one scale that is validated for assessing odor in neoplastic wounds, pointing towards the need to develop new instruments that incorporate validated and reliable instruments in clinical practice.